Ethylene and Abscisic Acid Signaling Pathways Differentially Influence Tomato Resistance to Combined Powdery Mildew and Salt Stress - Kissoudis, Christos; Seifi, Alireza; Yan, Zhe; Islam, A. T. M. Tanjimul; van der Schoot, Hanneke; van de Wiel, Clemens C. M.; Visser, Richard G. F.; van der Linden, C. G.; Bai, Yuling (Frontiers in Plant Science, 2017)
There is currently limited knowledge on the role of hormones in plants responses to combinations of abiotic and pathogen stress factors. This study focused on the response of tomato near-isogenic lines (NILs) that carry the Ol-1, ol-2 and Ol-4 loci, conferring resistance to tomato powdery mildew caused by Oidium neolycopersici, to combined powdery mildew and salt stress. These NILs were crossed with the notabilis (ABA-deficient), defenceless1 (JA-deficient), and epinastic (ET overproducer) tomato mutants to investigate possible roles of hormone signalling in response to combined stresses. In the NILs, marker genes for hormonal pathways showed differential expression patterns upon powdery mildew infection. The epinastic mutation resulted in breakdown of resistance in NIL-Ol-1 and NIL-ol-2. This was accompanied by reduced callose deposition, and was more pronounced under combined salt stress. The notabilis mutation resulted in H2O2 overproduction and reduced susceptibility to powdery mildew in NIL-Ol-1 under combined stress, but lead to higher plant growth reduction under salinity and combined stress. Resistance in NIL-ol-2 was compromised by the notabilis mutation, which was potentially caused by reduction of callose deposition. Under combined stress the compromised resistance in NIL-ol-2 was restored. Powdery mildew resistance in NIL-Ol-4 remained robust across all mutant and treatment combinations. Hormone signalling is critical to the response to combined stress and powdery mildew, in terms of resistance and plant fitness. ABA appears to be at the crossroads of disease susceptibility/senescence and plant performance under combined stress These gained insights can aid in narrowing down targets for improving crop performance under stress combinations.